Cosmic ray observations at high zenith angles - Vrana, A (1976)
The thesis is the description of the design and construction of a high zenith angle telescope for the Mawson observatory, together with some discussion of results obtained. Because the new Mawson observatory installed in 1972 is a logical extension complementing the high zenith angle experiment, it was felt that inclusion of a brief description of the new observatory complex would not be out of place. l joined the Australian National Antarctic Research Expedition in 1964 as an expedition physicist. During my stay at Mawson in 1965 I became aware of the shortcomings of mains operated electronic equipment at remote stations and designed some battery operated solid state circuits to replace the former circuitry. Upon my return from Mawson I was commissioned to finalise the design of the transistorised circuitry and develop modular circuit units for the use with counter telescopes. In 1966 a joint project was proposed by the Antarctic Division and the University of Tasmania for a high zenith angle ground based experiment. Given the basic requirements for the desired geometry I was to undertake the design, construction and installation of the new telescopes at Mawson. During the course of the work I realized that for a successful design an understanding of the principles of cosmic ray recording was necessary. Whilst the design of the experiment rested primarily on Dr. R.M. Jacklyn, I undertook the initial investigation of the air shower component influencing the observed intensity under the guidance of Dr. A.G. Fenton and Dr. R.M. Jacklyn. I sailed for Mawson in early 1968 to install and supervise the performance of the new telescope during the first year of operation. After my return to Hobart I carried out further tests regarding the air shower component as described in sec. 3.4, based on the original idea of Mr. G.C. Cooper, the Mawson physicist in 1969. In 1970 the Antarctic Division undertook to establish an underground observatory based on the proposal of Dr. R.M. Jacklyn. The design of the experiment ...